Spatiotemporal Progression of Microcalcification in the Hippocampal CA1 Region following Transient Forebrain Ischemia in Rats: An Ultrastructural Study. - Tae-Ryong Riew (PLoS ONE, 2016)
Calcification in areas of neuronal degeneration is a common finding in several neuropathological disorders including ischemic insults. Here, we performed a detailed examination of the onset and spatiotemporal profile of calcification in the CA1 region of the hippocampus, where neuronal death has been observed after transient forebrain ischemia. Histopathological examinations showed very little alizarin red staining in the CA1 pyramidal cell layer until day 28 after reperfusion, while prominent alizarin red staining was detected in CA1 dendritic subfields, particularly in the stratum radiatum, by 14 days after reperfusion. Electron microscopy using the osmium/potassium dichromate method and electron probe microanalysis revealed selective calcium deposits within the mitochondria of degenerating dendrites at as early as 7 days after reperfusion, with subsequent complete mineralization occurring throughout the dendrites, which then coalesced to form larger mineral conglomerates with the adjacent calcifying neurites by 14 days after reperfusion. Large calcifying deposits were frequently observed at 28 days after reperfusion, when they were closely associated with or completely engulfed by astrocytes. In contrast, no prominent calcification was observed in the somata of CA1 pyramidal neurons showing the characteristic features of necrotic cell death after ischemia, although what appeared to be calcified mitochondria were noted in some degenerated neurons that became dark and condensed. Thus, our data indicate that intrahippocampal calcification after ischemic insults initially occurs within the mitochondria of degenerating dendrites, which leads to the extensive calcification that is associated with ischemic injuries. These findings suggest that in degenerating neurons, the calcified mitochondria in the dendrites, rather than in the somata, may serve as the nidus for further calcium precipitation in the ischemic hippocampus.